Orthopedic surgery core curriculum hip and knee reconstruction - Wadey, Veronica M.R. (Canadian Medical Association, 2008)
OBJECTIVE: To develop a core curriculum for orthopedic surgery and to conduct a national survey to assess the importance of 281 curriculum items. Attention was focused on 55 topics pertaining to hip and knee reconstruction. METHODS: A 281-item curriculum was developed. We completed a content review and cross-sectional survey of a random selection of orthopedic surgeons whose primary affiliation was nonuniversity. We analyzed the data descriptively and quantitatively, using histograms, a modified Hotelling's T(2) statistic with the p value determined by a permutation test, and the Benjamini-Hochberg/Yekutieli procedure. Our analyses assumed that each respondent answered questions independently of the answers of any other respondent but that the answers to different questions by the same respondent might be dependent. RESULTS: Of 156 orthopedic surgeons, 131 (84%) participated in this study. Of 55 items ranked by all respondents, 42 received an average mean score greater than 3.5/4.0, and 51 received an average mean score equal to or greater than 3.0/40 (the standard deviation for each item ranged from 0.00 to 0.08), suggesting that 92.7% of the items are important or probably important to know by the end of residency. CONCLUSION: This study demonstrates agreement that it is important to include 92.7% of the items that pertain to hip and knee reconstruction in a core curriculum for orthopedic surgery. Residency training programs may need to ensure that appropriate educational opportunities focusing on complex primary and revision surgery are available to meet the future needs of orthopedic surgeons whose primary affiliation is nonuniversity.